Predictors of disease burden in patients with untreated transthyretin amyloid cardiomyopathy and their caregivers: a post hoc analysis of an international survey - Cappelli, Francesco; Ponti, Lucia; Hsu, Kristen; Damy, Thibaud; Villacorta, Eduardo; Verheyen, Nicolas; Keohane, Denis; Wang, Ronnie; Ines, Monica; Kumar, Nisith; Munteanu, Carmen (Frontiers in Cardiovascular Medicine, 2025)
IntroductionTransthyretin amyloid cardiomyopathy (ATTR-CM) is a progressive condition with debilitating symptoms. The self-reported burden of ATTR-CM on patients and their caregivers was previously evaluated in an international, multicenter, real-world survey study.MethodsThis post hoc analysis used univariate and multivariate models to evaluate survey items as predictors of ATTR-CM burden. The final multivariate models were optimized using forward selection and CV Press criteria with 8-fold cross-validation to include only the best predictors. Hierarchical linear regression analyses were used to explore potential moderators of the relationship between patient health status and caregiver burden.ResultsThe original survey included 208 patients with ATTR-CM, naïve to disease-modifying treatment, and their unpaid primary caregivers from international amyloidosis centers of excellence in 7 countries between July 2021 and August 2022. Most patients were male (86%), elderly (median age, 81 years), and had untreated wild-type ATTR-CM (91% of 155 with genetic testing). Patients reported fair to good health status overall [Kansas City Cardiomyopathy Questionnaire Overall Summary (KCCQ-OS) median score, 68]. Most (60%) of the 199 patients with a New York Heart Association (NYHA) classification were class II (18% class I; 22% class III). Optimized multivariate models for several measures found symptomatic heart failure (NYHA class II or III), having “weakness, especially in the legs,” older age, and female sex, were independent predictors of higher patient-reported burden. The majority of caregivers were female (85%) and the spouse (59%) or adult child (37%) of the patient. The median duration of caregiving was 1.5 years. In the final optimized multivariate model, only the patient's KCCQ-OS score was a significant predictor of caregiver burden. This relationship was not clinically moderated by other patient or caregiver variables.ConclusionsOur analysis showed that heart failure symptoms, weakness, especially in the legs, older age, and female sex, are independent predictors of higher disease burden in patients with ATTR-CM. A higher caregiver burden was best predicted by poorer health status in the patient, even in the presence of potential moderators. Implementing strategies to reduce the physical symptoms experienced by patients with ATTR-CM may help to reduce their burden, and that experienced by caregivers.